Pharmaceutically Active Microbial AhR Agonists as Innovative Biodrugs in Inflammation - Matteo Puccetti; Marilena Pariano; Claudio Costantini; Stefano Giovagnoli; Maurizio Ricci (MDPI AG, 2022)
Alterations of the microbiome occur in inflammatory and autoimmune diseases, a finding consistent with the role of the microbiome in the maintenance of the immune system homeostasis. In this regard, L-tryptophan (Trp) metabolites, of both host and microbial origin, act as important regulators of host-microbial symbiosis by acting as aryl hydrocarbon receptor (AhR) ligands. The intestinal and respiratory barriers are very sensitive to AhR activity, suggesting that AhR modulation could be a therapeutic option to maintain the integrity of the epithelial barrier, which has substantial implications for health even beyond the mucosal site. A number of studies have highlighted the capacity of AhR to respond to indoles and indolyl metabolites, thus positioning AhR as a candidate indole receptor. However, the context-and ligand-dependent activity of AhR requires one to resort to suitable biopharmaceutical formulations to enable site-specific drug delivery in order to achieve therapeutic effectiveness, decrease unwanted toxicities and prevent off-target effects. In this review, we highlight the dual activity of the microbial metabolite indole-3-aldehyde at the host-microbe interface and its ability to orchestrate host pathophysiology and microbial symbiosis and discuss how its proper clinical development may turn into a valuable therapeutic strategy in local and distant inflammatory diseases.